Histopathological of Brain, Eye, Liver, Spleen Organs of Grouper Suspected VNN in Penyambuan Village, North Lombok - Agustina Rahmawanti; Dewi NurÃ¢â¬â¢aini Setyowati; Alis Mukhlis (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Cantang grouper is one of the leading NTB commodities that have high economic value. Cantang grouper (Epinephelus fuscoguttatus) has a wide distribution, one of which is in Penyambuan Village, North Lombok Regency. The disease that often attacks grouper fish is VNN (Viral Nervous Necrosis). One of the methods that can be used to detect VNN is the histopathological method. The purpose of this study was to determine the suspected cases and levels of infection with the VNN (Viral Nervous Necrosis) virus in grouper fish (Epinephelus fuscoguttatus) cultivated in Penyambuan Hamlet, Tanjung District, North Lombok Regency by using the histopathological method. The research method used is descriptive by explaining the results obtained from the histopathological test of 3 samples taken by looking at the presence or absence of necrosis in the eye and brain organs of the test sample. The results of observations using a microscope on the test sample after the histopathological process showed that the second sample (S2) of cantang grouper from the KJA in Pemambuan was suspected to be positive for VNN infection, as seen from the presence of necrosis in the form of vacuoles in the brain and eye organs in the level of chronic infection. From the results of this study, it is suggested that further research be carried out in the form of confirmation of the results using a more accurate method, namely real-time PCR. This study can serve as a detection guide for samples of suspected VNN.